(untitled) (Comprehensive Journal of Science, 2025)
The Libyan construction sector faces chronic challenges, including schedule delays, cost overruns, and inefficiencies stemming from political instability and limited technology adoption. This study assesses the potential of integrating Building Information Modeling (BIM), Internet of Things (IoT), and Artificial Intelligence (AI) with Integrated Project Delivery (IPD) to enhance schedule compliance. Employing a quantitative approach, a structured survey was distributed to 150 construction professionals in Libya, yielding 120 valid responses (80% response rate). Data analysis was conducted using SPSS, incorporating descriptive statistics and multiple linear regression. Results indicate high familiarity with BIM (67.5% familiar or very familiar), but lower for AI (47.5% unfamiliar or slightly familiar) and IPD (40.8%). Perceived impact on schedule compliance was positive, with BIM rated highest (77.5% high or very high impact). Key barriers include high implementation costs (92.5%) and skill shortages (84.1%). Regression analysis revealed a significant negative relationship between knowledge level and perceived impact (β = -0.374, p < 0.001), suggesting that more knowledgeable professionals adopt a more realistic view of contextual challenges. The study recommends training programs, government incentives, and phased adoption to foster digital transformation, contributing to the sector’s recovery in Libya.